2009
DOI: 10.1088/0022-3727/42/6/065303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth temperature on formation of continuous Ag thin film on ZnO surface by ultra-high vacuum deposition

Abstract: Growth of an Ag film on a ZnO (0 0 0 1) surface by ultra-high vacuum deposition has been investigated by field emission scanning electron microscopy. It is revealed that the growth temperature has a considerable effect on the formation of a continuous Ag thin film on a ZnO surface. At room temperature or above, the formation of continuous Ag films with small thickness was found to be difficult due to an upstepping mechanism, whereas a continuous Ag film as thin as 30 nm was achieved at 140 K, resulting from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Figure 1(a) shows the morphology of the Ag layer containing Ag nanoparticles with an average size of ∼20 nm. Our previous studies have demonstrated that the size and density of Ag particles can be delicately controlled by the growth temperature and deposition time [17]. Here, we find that the Ag particle size plays a key role in determining the size of the consequent ZnO nanorod grown by the Ag catalyst-driven method.…”
Section: Resultsmentioning
confidence: 53%
“…Figure 1(a) shows the morphology of the Ag layer containing Ag nanoparticles with an average size of ∼20 nm. Our previous studies have demonstrated that the size and density of Ag particles can be delicately controlled by the growth temperature and deposition time [17]. Here, we find that the Ag particle size plays a key role in determining the size of the consequent ZnO nanorod grown by the Ag catalyst-driven method.…”
Section: Resultsmentioning
confidence: 53%
“…It is well known that continuous metal films can grow at ultralow thicknesses using very low temperatures, although an unfavorable shift in the final morphological features to fine and irregular crystallinities is an ineluctable consequence . Researchers have reported the reinforcement of layer‐by‐layer growth behavior of transitional and noble metals with a decrease in the substrate temperature to as low as less than 100 K (Table ) . These results can be explained by a simple scenario of surface dynamics.…”
Section: Technical Issues In Ultrathin Metal Film Growthmentioning
confidence: 99%
“…However, the most common technique is the physical vapour deposition (PVD), such as thermal evaporation, e-beam evaporation and sputtering [7,14]. Using our dual thermal/e-beam evaporation system enabled us to evaporate (KVE-ENT 200hl Korea Vacuum Tech), in the same vacuum chamber, up to four different materials through electron beam evaporation and one additional material via thermal evaporation.…”
Section: Simulation and Experimental Setupmentioning
confidence: 99%
“…Many investigations on metal-dielectric multilayer film structures have been performed during the last two decades [6,7], which is due to the unique combination of the optical and thermal properties of metal. Several material systems suitable for use in metal-dielectric multilayer coatings, for example, Ti02/Ag/Ti02, or Zr02/Ag/Ti02 [6], as well as WOiAgIW03 [1] have been reported.…”
Section: Introductionmentioning
confidence: 99%